Human trafficking and slavery offenders in Australia - Frances Simmons
This paper provides an assessment of offenders who commit human trafficking, slavery and slave-like crimes in Australia. Foreword: There is a lack of international and Australian research about offenders who have been convicted of human trafficking, slavery and slave-like practices. In Australia, 15 offenders have been convicted of such crimes. The publicly available court judgments about these offenders contain invaluable information about the characteristics and motivations of offenders, the intersection of trafficking offending with other forms of criminality and the common methods offenders use to control and exploit their victims. By analysing these cases, this paper provides an accessible and timely assessment of offenders who commit human trafficking, slavery and slave-like crimes in Australia. This paper is part of a wider program of research undertaken by the AIC on this type of crime in Australia and the Asia–Pacific region, which is funded by the Australian Government as part of its national Action Plan to Eradicate Trafficking in Persons. Authored by Frances Simmons, Brynn O’Brien, Fiona David and Laura Beacroft